Hospitalization due to cancer among German seafarers. Issue 4 (24th February 2015) - Oldenburg, Marcus; Harth, Volker; Manuwald, Ulf
Abstract : Objectives: To evaluate the relative risk of cancer among male German seafarers employed on German vessels in respect of various shipboard ranks and types of vessel. Methods: The seafarers' cancer discharge diagnoses from hospital were compared with those discharge diagnoses from the German general population and expressed as a standardized hospitalization ratio (SHR). Results: The examined seafarers (on average 23, 436 per year) showed a higher SHR for malignant neoplasms at all sites, in decreasing order for leukemia, non‐Hodgkin lymphoma (NHL), respiratory cancer, and non‐melanoma skin cancer. Seafarers employed on tankers showed a considerably elevated SHR for malignant neoplasms at all sites, which was mainly attributable to their high SHR for leukemia and respiratory cancer. Conclusions: Seafaring occupations pose an elevated risk of certain cancers. Further studies are required to evaluate to what extent occupational exposure to carcinogenic substances and lifestyle‐related unhealthy behaviours contribute to the increased risk of cancer in seafarers. Am. J. Ind. Med. 58:456–463, 2015. © 2015 Wiley Periodicals, Inc.